Outcomes Following the Plantar Condylectomy for the Management of Plantar Plate Injuries: A Retrospective Review - Alan P. Samsonov BS; James J. Butler MB BCh BAO; John G. Kennedy MD, MCh, MMSc, FFSEM, FRCS (Orth) (Foot & Ankle Orthopaedics)
Category: Sports; Midfoot/Forefoot Introduction/Purpose: The purpose of this study was to evaluate outcomes following outcomes following plantar condylectomy for the management of plantar plate injuries. Methods: Retrospective chart review identified 20 patients who underwent a PRP injection for the treatment of plantar plate injuries. Pre-operative magnetic resonance imaging (MRI) scans were obtained and the grade of the plantar plate injury was recorded. Clinical outcomes assessed included: pre- and post-operative foot and ankle outcome score (FAOS), visual analog scale (VAS), complications, failures, secondary surgical procedures, and return to sport data. Results: Twenty patients with a mean follow-up time of 32.1±7.8 months were included. There were 0 patients that were grade 1, 5 patients were grade 2 (25.0%) and 15 patients were grade 3 (75.0%). There was a statistically significant improvement in both FAOS (58.1 -> 91.4) and VAS scores (6.5 -> 1.8) following plantar condylectomy for the management of plantar plate injuries. No complications were observed. There was 1 failure, which underwent a scorpion procedure at 15.6 months following plantar condylectomy. 15 patients played sport pre-operatively, all of which (100%) returned to sport at a mean time of 7.5 weeks following plantar condylectomy. Conclusion: This retrospective review demonstrated improvement clinical and functional outcomes following plantar condylectomy for plantar plate injuries. There was a 100% return to sport rate at a mean time of 7.5 weeks. The failure rate was 5.0%. Further comparative studies with longer follow-up are warranted to determine the precise role of plantar condylectomy for the management of plantar plate injuries.